Desenvolviment(ism)o, descolonialidade e a geo-história da administração no Brasil: a atuação da CEPAL e do ISEB como instituições de ensino e pesquisa em nível de pós-graduação - Wanderley, Sergio Eduardo de Pinho Velho (2015)
The objective of this dissertation is to investigate how the Economic Commission for Latin America (ECLA) and Superior Institute of Brazilian Studies (ISEB) have contributed to management history in Brazil. This dissertation departed from a consolidated historiography methodology, but employed the decolonial perspective to problematize the term history and, thus, proposes a new investigation agenda. The importation of historiography themes such as Americanization and Cold War fosters the mimicry of investigation agendas that subalternizes other local processes that have contributed to management historiography. The geo-historical investigation is carried out from the interaction of the two concepts of development(alism) that emerge from the literature review – one that emerges from the Latin American reality and the other received externally via Americanization – that come closer or get further away from each other, and that are inserted in the long durée of Latin America modernity/coloniality. The search for management science began, in Brazil, in connection with the modernization and development of the country that led to the creation of the first graduate management schools and the courses object of this dissertation, which formed 1.316 professionals at postgraduate level. During this period, the role of Americanization should be minimized and one should relativize the role of management schools in management geo-history. The aim is to bring to the fore knowledges belonging to the tradition of the Latin American social critical thought - subalternized by management literature - that can inform the area in Brazil and abroad. This is a way to decolonize historiography investigation agendas and to eschew the tendency of acritically repeating foreign content.